EFEKTIVITAS PELATIHAN PROGRAM GENRE TERHADAP KETERAMPILAN SEBAGAI PENDIDIK SEBAYA PADA REMAJA DI KABUPATEN JEMBER: The Effectiveness of the GenRe Training Program on Skills as Peer Educators for Adolescents in Jember Regency - Hidayat, Nabil Mumtaz; Wahyuni A, Sri; Asih, Susi Wahyuning (Forind Press, 2024)
Teenage behavior has changed a lot along with changing times and technological developments. These changes are more likely to be in a negative direction. Based on conditions like these, teenagers need information about reproductive health and useful activities, which is why the role of Peer Educators (PS) is needed. Method used in this research is the simplest pre-experimental and does not have a control group, with a One-shot Case Study Research Design approach, with a sample size of 62 Peer Educators. This research was conducted in June 2024, using the Peer Educator Achievement Indicator Checklist instrument. Data analysis used Paired T-Test with a value of α = 0.05. The results of the research show that before the training using the social skills training module method the average score was 72.43 and after being trained using the social skills training module method it was 83.83. The effectiveness of the GenRe training program using the social skills training module method on the skills of Peer Educators obtained a p value of 0.000. The conclusion from this research is the GenRe Training Program is effective in improving the skills of Peer Educators (PE). GenRe program training can be carried out on an ongoing basis to improve the skills of Peer Educators in providing education to their peers.